Incidence of Adjuvant Radiation Therapy after Radical Hysterectomy and Preoperative Prognostic Factors in Cervical Cancer Patients (Stage IA2-IIA1) in Lampang Hospital, Ten Years’ Experience - Buapaichit, Kuanoon; Choyrum, Salisa; Sowala, Nattaya; Makee, Poranee; Sing-on, Nattida (Greater Mekong Subregion Medical Journal, 2025)
Introduction: For early-stage cervical cancer (IA2–IIA1), radical hysterectomy with pelvic lymphadenectomy and primary chemoradiation offer comparable cure rates. However, some patients require adjuvant radiation therapy after surgery. Combined modality therapy can lead to significant long-term complications. Objectives: The objective of this study is to evaluate the incidence of adjuvant radiation therapy after radical hysterectomy and to identify preoperative prognostic factors in early-stage cervical cancer (stages IA2–IIA1) at Lampang Hospital. Materials and Method: This retrospective cohort study included early-stage cervical cancer patients who underwent radical hysterectomy with pelvic lymphadenectomy (2014–2023). Preoperative risk factors for adjuvant radiotherapy, including tumor size, diagnostic method, tumor type, vaginal bleeding, and suspected vaginal invasion, were analyzed using univariate and multivariate logistic regression in Stata 18.0. Results: Out of 173 patients, 69 (39.9%) received postoperative adjuvant radiotherapy. Preoperative vaginal bleeding (aOR 2.48, 95% CI: 1.21-5.06; p = 0.013) and suspected vaginal invasion (aOR 10.92, 95% CI: 1.23-97.09; p = 0.032) were significantly associated with the need for adjuvant radiation therapy after radical hysterectomy. Tumor size > 4 cm was associated with an increased risk in the univariable analysis (OR 2.76, p = 0.016). Other factors, including non-SCCA histology and gross lesions, showed trends toward increased risk but did not reach statistical significance. Conclusion: At Lampang Hospital, 39.9% of patients received postoperative radiation therapy after radical hysterectomy. Preoperative clinical examinations alone are insufficient to predict radiation therapy needs. Advanced imaging techniques, such as CT or MRI, are used to aid in treatment planning. In resource-limited settings, evaluations should focus on high-risk patients with vaginal bleeding, suspected vaginal invasion, or tumors > 4 cm.